Skeletal muscle metabolism during prolonged exercise in Pompe disease. Issue 6 (August 2017) - Preisler, Nicolai; Laforêt, Pascal; Madsen, Karen Lindhardt; Husu, Edith; Vissing, Christoffer Rasmus; Hedermann, Gitte; Galbo, Henrik; Lindberg, Christopher; Vissing, John
Abstract : Objective: Pompe disease (glycogenosis type II) is caused by lysosomal alpha-glucosidase deficiency, which leads to a block in intra-lysosomal glycogen breakdown. In spite of enzyme replacement therapy, Pompe disease continues to be a progressive metabolic myopathy. Considering the health benefits of exercise, it is important in Pompe disease to acquire more information about muscle substrate use during exercise. Methods: Seven adults with Pompe disease were matched to a healthy control group (1:1). We determined (1) peak oxidative capacity (VO2peak ) and (2) carbohydrate and fatty acid metabolism during submaximal exercise (33 W) for 1 h, using cycle-ergometer exercise, indirect calorimetry and stable isotopes. Results: In the patients, VO2peak was less than half of average control values; mean difference −1659 mL/min (CI: −2450 to −867, P = 0.001). However, the respiratory exchange ratio increased to >1.0 and lactate levels rose 5-fold in the patients, indicating significant glycolytic flux. In line with this, during submaximal exercise, the rates of oxidation (ROX) of carbohydrates and palmitate were similar between patients and controls (mean difference 0.226 g/min (CI: 0.611 to −0.078, P = 0.318) and mean difference 0.016 µmol/kg/min (CI: 1.287 to −1.255, P = 0.710), respectively). Conclusion: Reflecting muscle weakness and wasting, Pompe disease is associated with markedly reduced maximal exercise capacity. However, glycogenolysis is not impaired in exercise. Unlike in other metabolic myopathies, skeletal muscle substrate use during exercise is normal in Pompe disease rendering exercise less complicated for e.g. medical or recreational purposes.